Shape-shifters: Romantic-era representations of the child in the Wollstonecraft-Godwin family circle - Roy, M (2008)
This thesis is a study of the representations of childhood in the works of the family circle of Mary Wollstonecraft and William Godwin and their intellectual inheritors, Mary Shelley and Percy Bysshe Shelley. It argues that their literary representations of the child, as a group, form an index of their political resistance to the dominant cultures of their era. The thesis situates these representations of childhood against the backdrop of the Romantic-era cultural celebration of childhood as established in works by historians and critics such as Philippe Ariés and James McGavran, Jr. It argues that the new sentimental category of the child established in the writings of Rousseau and Wordsworth, paradoxically, tends to marginalise the child from the socially powerful world of adults, even while establishing the child’s new specificity. This ethical impasse is resolved by the Wollstonecraft-Godwin family circle through its literary representations of the child, where the child becomes a shifting metaphor for all socially oppressed groups. Moreover, the adult author invites the child to participate in the world of adult power, eschewing a totalising adult perspective that erases the child’s specific concerns. This thesis tracks the development of the versions of the child in the works of the Wollstonecraft-Godwin family circle, from their early, discursive, political works such as Wollstonecraft’s A Vindication of the Rights of Woman and Godwin’s Political Justice, where they represent their late-eighteenth century ideals of political emancipation through the education of the child, to more imaginative versions of the child in their later works. I locate a moment in each writer’s career at which the adult-child divide observed in their early works collapses: their doubts about rationalist epistemology crystallise, and they switch to open-ended modes of discourse in literary genres such as novels, which allow more freedom for the coded expression of radical political ideas through the representations of the child. In their later works, especially in Godwin’s radical publications for children, the adult-child hierarchy is dissolved: the child becomes a complex metaphor, representing the varied political concerns of disempowered adults and children. The discussion concludes with a sketch of the imaginative appropriation and transformation of the Wollstonecraft-Godwin representations by the Shelleys. Mary Shelley, and to a lesser extent, Percy Bysshe Shelley, adapt the radicalism of their predecessors’ literary representations of the child to suit their own altered socio-political contexts.